A review of the whitefly genus Aleurocanthus Quaintance & Baker (Hemiptera: Aleyrodidae) from China, with description of two new species and two new records - Lin, Qing-Song; Lu, Lin-Qian; Zhang, Xiao; Dubey, Anil Kumar; Wang, Ji-Rui (Zootaxa, 2026)
The whitefly genus Aleurocanthus Quaintance & Baker is revised from China. Two new species viz., A. latifolii sp. nov. and A. macropodi sp. nov., are described and illustrated. Aleurocanthus chiengmaiensis Takahashi and A. clitoriae Jesudasan and David are recorded for the first time from China. The occurrence of an undescribed Aleurocanthus species in China is documented. Sexual dimorphism observed in the puparia of A. clitoriae is presented. New host plant records are indicated. An identification key to the puparia of Aleurocanthus species known from China is provided.